Optimal integration of wind energy with a shunt-FACTS controller for reductions in electrical power loss - I Made Wartana; Ni Putu Agustini; Sasidharan Sreedharan (Institute of Advanced Engineering and Science, 2021)
The integration of distributed generators (DGs) with flexible alternating current transmission systems (FACTS) can improve the performance of the grid system. In this study, we determine the location and optimal size of one type of DG, based on wind energy, with a shunt-FACTS control device called a static var compensator (SVC). The voltage profile is increase and the power loss reduced due to an improvement in performance from the maximizing load bus system scenario. Newton-Raphson power flow with a wind turbine generator (WTG) and SVC are formulated as a multi-objective problem called MLB system and minimizing system power loss (Ploss) by satisfying various system constraints, namely the loading limits, generation limits, voltage limits, and the small-signal stability. A variant of the genetic algorithm, called the non-dominated sorting genetic algorithm II (NSGA-II), is used to solve these conflicting multi-objective optimization problems. Modifications to the IEEE 14-bus standard and practical test system integrated to the WTG and SVC in the PSAT software are used as a test system. The simulation results indicate that the optimal allocation of the WTG and SVC, determined using the proposed technique, results in improved system performance, since all the specified constraints are met.